A dose-ranging study of rapacuronium in pediatric patients - Meakin, George H.; Motsch, Johann; Schönstedt, Rüdiger (Anesthesiology, 2000)
BACKGROUND: The aim of this study was to determine the dose or doses of the new rapid-onset, short-acting, neuromuscular blocking drug rapacuronium that would provide satisfactory conditions for tracheal intubation at 60 s in infants and children. METHODS: Sixty-five infants (< 1 yr), 51 younger children (1-6 yr), and 49 older children (7-12 yr) were studied. Anesthesia was induced with thiopental-nitrous oxide-oxygen. Tracheal intubation was attempted 60 s after administration of one of five doses of rapacuronium (0.5, 1.0, 1.5, 2.0, or 2.5 mg/kg) and intubating conditions were assessed using a four-point scale. Following tracheal intubation, anesthesia was maintained with nitrous oxide-oxygen and alfentanil (12.5-50 microg/kg) as necessary. Neuromuscular transmission was monitored in an uncalibrated fashion using an acceleromyograph. RESULTS: Intubating conditions were good or excellent at 60 s in all infants after doses of 1.5 mg/kg or more and in all younger and older children after doses of 2.0 mg/kg or more. The duration of action of rapacuronium was dose- and age-dependent. Mean times to reappearance of the third twitch of the train-of-four (TOF; T3) were less than 10 min in infants at doses of 1.5 mg/kg or less and in younger and older children at doses of 2.0 mg/kg or less. Recovery of T3 after 1.0-2.0 mg/kg rapacuronium was significantly slower in infants compared with younger (P = 0.001) and older (P = 0.02) children. Five adverse experiences were related to rapacuronium administration: Bronchospasm (two instances), tachycardia (one instance), and increased salivation (two instances). None were serious. CONCLUSIONS: Doses of 1.5 and 2.0 mg/kg rapacuronium can produce satisfactory intubating conditions at 60 s in anesthetized infants and children, respectively, and are associated with a short duration of action.